2018
DOI: 10.1371/journal.pone.0190639
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in extreme activism in support of others’ political struggles: The role of politically motivated fusion with out-groups

Abstract: Humans are a coalitional, parochial species. Yet, extreme actions of solidarity are sometimes taken for distant or unrelated groups. What motivates people to become solidary with groups to which they do not belong originally? Here, we demonstrate that such distant solidarity can occur when the perceived treatment of an out-group clashes with one’s political beliefs (e.g., for Leftists, oppressive occupation of the out-group) and that it is driven by fusion (or a feeling of oneness) with distant others with who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 68 publications
(114 reference statements)
0
54
0
5
Order By: Relevance
“…One of the most fundamental innovations of this period is the notion that it is possible to be fused with different types of entities. In addition to the traditional conception of identity fusion, as the relation that an individual develops with a group (the ingroup, but also an outgroup that, e.g., is oppressed, see Kunst et al, 2018), people can fuse with another individual as his/her romantic partner (Joo & Park, 2017; Walsh & Neff, 2018), his/her sibling (Vázquez, Gómez, Ordoñana, Swann, & Whitehouse, 2017), or a political leader (Kunst, Dovidio, & Thomsen, 2019). But individuals can also fuse with an animal (Buhrmester, Burnham, et al, 2018), a trademark (Hawkins, 2019), or a value or conviction , as religion (Fredman, Bastian, & Swann, 2017).…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most fundamental innovations of this period is the notion that it is possible to be fused with different types of entities. In addition to the traditional conception of identity fusion, as the relation that an individual develops with a group (the ingroup, but also an outgroup that, e.g., is oppressed, see Kunst et al, 2018), people can fuse with another individual as his/her romantic partner (Joo & Park, 2017; Walsh & Neff, 2018), his/her sibling (Vázquez, Gómez, Ordoñana, Swann, & Whitehouse, 2017), or a political leader (Kunst, Dovidio, & Thomsen, 2019). But individuals can also fuse with an animal (Buhrmester, Burnham, et al, 2018), a trademark (Hawkins, 2019), or a value or conviction , as religion (Fredman, Bastian, & Swann, 2017).…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…Several researchers have found other potential causes of fusion. Kunst et al (2018) showed that political struggles (e.g., oppressive occupation of the outgroup) that clash with people's political beliefs might lead to fusion with groups to which individuals do not belong. Carnes and Lickel's (2018) manifest that perceiving that the group shares core moral beliefs or convictions can also cause fusion.…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
See 3 more Smart Citations